Control of Be capsule low mode implosions symmetry at the National Ignition Facility. (May 2016) - Kyrala, G A; Kline, J L; Yi, S; Simakov, A N; Olson, R E; Wilson, D C; Batha, S; Dewald, E L; Tommasini, R; Ralph, J E; MacPhee, A G; Callahan, D A; et al.
Abstract: We present results of the beryllium experimental campaign on the implosion symmetry properties of beryllium capsules at the National Ignition Facility (NIF) [1]. These indirect drive experiments measure both the inflight and core self-emission implosion symmetry. The inflight symmetry of the ablator before stagnation is measured using a backlight imaging technique. A copper backlighter was used to measure the transmissions (or backlit absorption) of the copper doped beryllium shells. Images of the x-ray emission from the core around bang time provide a measure of the symmetry near peak compression. Both pieces of information about the 2D symmetry are used to infer the drive and velocity uniformity enabling us to predictably adjust the properties of the incident laser, mainly the time dependent ratio of the inner beam cone power to the outer laser beam powers, to achieve proper symmetry of the implosion. Results from these experiments show inner beam propagation is not degraded compared to similar implosions with CH ablators. Variations in the shape compared with implosions using CH ablators also provides information about the cross beam energy transfer used to adjust the equatorial shape and thus infer information about the differences in plasma conditions near the laser entrance holes. Experimental results of the implosion shape for beryllium capsules will be presented along with comparisons relative to CH ablators.